Pengembangan Lembar Kerja Peserta Didik Berbasis Augmented Reality Berbantuan Assemblr Edu - Restina Purba; Choms Gary Ganda Tua Sibarani; Andri Zainal; Weny Nurwendari; Ulfa Nurhayani (Jurnal Muara Pendidikan, 2026)
This research was driven by the lack of student enthusiasm in Accounting lessons. It aims to outline both the validity of a student worksheet (LKPD) integrated with Augmented Reality (AR) technology and the reactions of students upon utilizing it. The study took place during the 2025/2026 academic term at SMK Negeri 7 Medan. A limited trial was conducted involving 10 eleventh-grade students from the AKL 3 class, focusing specifically on an AR-supported LKPD covering the worksheet (neraca lajur) material.The methodology applied was Research and Development (R&D) following the 4D framework (Define, Design, Develop, Disseminate). Information was gathered via interviews, observations, questionnaires, and documentation. The educational product underwent expert appraisal by content and media specialists, alongside a teaching practitioner, prior to student testing. Findings revealed that the designed LKPD achieved a highly valid status. Evaluation scores stood at 88% from content specialists, 90.66% from media experts, and 91.11% from the educator. Furthermore, student feedback during the limited trial recorded an 88.88% approval rate, falling into the very good category. Consequently, the AR-integrated LKPD is deemed highly appropriate and feasible for facilitating Accounting instruction, most notably for the worksheet topic.